Protegendo vidas e garantindo direitos: a prática da proteção integral no programa de proteção a crianças e adolescentes ameaçados de morte no Estado da Paraíba - Melo, Érica Renata Chaves Araújo de (2020)
This study aims at analyzing if the Death Threat Protection Program for Children and Adolescents (PPCAAM) of the state of Paraíba, Brazil, actually promotes Integral Protection as established by the Children‟s and Adolescents‟ Statute (ECA). The present study describes the historical paths to the consolidation of children‟s and adolescents‟ rights, through an analysis of both national and international main guidelines that have based the Integral Protection Doctrine, the Convention and the Declaration of Rights of the Child as well as the Federal Constitution of Brazil of 1988 and the Children‟s and Adolescents‟ Statute of 1990. This study highlights the debate over contributing factors to lethal violence against children and adolescents, by gathering statistical data from the Adolescents‟ Homicide Index (IHA) and the Violence Map, whilst discussing Capitalism and the State, Education on Human Rights and Public Policies. In order to do as described, PPCAM‟s creation and current functioning as an institutional policy to tackle children and juvenile lethal violence in the state of Paraíba were contextualized by gathering national and other states‟ data on children and juvenile protection. This consists of a qualitative study of an exploratory level, based on the dialectical method. Gathered data was analyzed using Bardin‟s (1977) content analysis technique, which was utilized on both the documental analysis of the Individual Assistance Plan (PIA), Field Notes/Attendance Records, as well as on 07 (seven) semi-structured interviews with members of PPCAM‟s professionals. As part of this research‟s corpus, 06 (six) case studies have been selected, conditioned by the type of protection as well as their attendance to the program, from 2013 to 2018. Three major factors were identified as contributing to the denying of Integral Protection of the PPCAAM in the state of Paraíba: the program‟s national execution by presidential decreet; the lack of available places on the highly complex state network, specifically designated to the program; and the actual denial of certain fundamental rights, which harms Human Right‟s principles of integrality, interdependency, and indivisibility. The study proposes alternatives aimed to contribute to improving PPCAMS‟s execution in the state of Paraíba, whilst primary information regarding the program is gathered, enabling further discussions.